A Sr-isotopic investigation of bifurcating chromitite layers of the UG1 at the Impala Platinum Mine, Rustenburg - Nyakane, Tshepo Felix (University of the Free State, 2023)
Chromitite bifurcations hosted within, but not limited to, the Upper Group 1 (UG1) chromitite layer in the Critical Zone of the Bushveld Complex are one of the most enigmatic geological features encountered. Several researchers have attempted to develop models explaining how these bifurcations could have been formed. Most of these studies were heavily based on field observation with little to no geochemical data to support their findings. In this study, samples of an exposure of chromitite bifurcations from the UG1 chromitite at Shaft No.11 of Impala Platinum Limited in the Western Limb of the Bushveld Complex were utilised to perform petrographic and geochemical work including Sr-isotopic determinations on plagioclase. The geochemical data collected, along with field observations, were used to develop a conceptual model explaining the development of the bifurcations. Four sample cuts (D, C, B, and A) across the anorthositic footwall of the UG1 chromitite, each with a width of 10 cm and varying lengths were sampled from the study area using a diamond saw. The sample cuts represent vertical transects across a set of bifurcating chromitite layers, taken approximately 1 m apart, on the northern side of the approximately 40 m section. Thirty-four polished thin sections were made representing all the sample cuts. The polished thin sections were studied petrographically with an Olympus BX51 microscope. Electron microprobe analyses were carried out to obtain the compositions of chromite and plagioclase crystals from the samples, and Laser Ablation Multi-Collector Inductively Coupled Mass Spectrometry was used to obtain in-situ isotopic compositions of the plagioclase crystals. Plagioclase in the anorthosite layers exhibits very little variation in An% with average values of 75.10 ± 3.27, 74.26 ± 1.93, 75.10 ± 3.27 and 73.85 ± 1.89 for sample cut D to A, respectively. Plagioclase in the chromitite layers reveals much more significant variation in An% with average values of 70.69 ± 14.15, 78.16 ± 15.26, 56.49 ± 33.13 and 55.50 ± 36.68 for sample cuts D to A, respectively. The in-situ plagioclase isotopic composition reveals that the initial ⁸⁷Sr/⁸⁶Sr ratios of plagioclase in anorthosite show very little variation both vertically and laterally through sample cuts A to D, with an average value of 0.7062 and individual layers that are generally within error compared to adjacent layers. Most chromitite layers also display ⁸⁷Sr/⁸⁶Sr ratios that are comparable to those observed in the anorthosite, although some of the thicker layers returned values that are more radiogenic, e.g., the bottom thick layer in sample cut A, which returned values on the order of 0.709 – 0.710. Taking into account the field relations along with the petrography and geochemistry of the study area, it is envisaged that the chromitite bifurcations in the study area were formed in the following stages: (1) Development of an irregular floor through the thermo-chemical erosion of the underlying anorthosite footwall. (2) The intrusion of chromite-rich slurry (mass balance requirement) as a basal flow resulted in thick chromitite layer deposition on an uneven surface. (3) Development of cyclic anorthosite and chromitite forming bifurcations. Pressure fluctuations (magma influxes, roof rupturing events, shock waves) permitted rapid transitions between the system's chromitite and plagioclase stability fields. A large reservoir of melt likely buffered compositional and isotopic changes. (4) The intrusion of a chromite-rich slurry led to renewed erosion and formation of the thick upper chromitite layer, with the thin chromitite layers now appearing as offshoots from the base of this layer. (5) Downward intrusion of slurry into rheologically weak zones led to the development of additional bifurcations.
Dissertation (M.Sc.(Geology))--University of the Free State, 2023
Keywords: Geochemistry, South Africa; Bushveld Complex, South Africa; Isotopic compositions; Chromitite; Anorthosite; Geological bifurcations